2007
DOI: 10.1016/j.bbrc.2007.08.104
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin—A new adipokine that modulates adipogenesis via its own receptor

Abstract: Chemerin, an 18 kDa protein secreted by adipose tissue, was reported to modulate immune system function through its binding to the chemerin receptor (chemerinR). We herein demonstrate that chemerin also influences adipose cell function. Our data showed 5 that chemerin and chemerinR mRNA expressions were highly expressed in adipose tissues, and that their expression levels were up-regulated in mice fed a high-fat diet. Both chemerin and chemerinR mRNA expression dramatically increased during the differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
251
3
16

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 317 publications
(289 citation statements)
references
References 27 publications
10
251
3
16
Order By: Relevance
“…Furthermore, there have been reports with conflicting results where chemerin expression was examined as a function of insulin sensitivity in response to thiazolidinediones (TZDs). Whereas some studies suggested that using these insulin sensitizers was associated with elevated chemerin expression (Roh et al, 2007), others reported the opposite (Vernochet et al, 2009;. Our results suggest that among the studied group of adult Saudis, chemerin is not a clear marker of insulin resistance.…”
Section: Discussioncontrasting
confidence: 53%
“…Furthermore, there have been reports with conflicting results where chemerin expression was examined as a function of insulin sensitivity in response to thiazolidinediones (TZDs). Whereas some studies suggested that using these insulin sensitizers was associated with elevated chemerin expression (Roh et al, 2007), others reported the opposite (Vernochet et al, 2009;. Our results suggest that among the studied group of adult Saudis, chemerin is not a clear marker of insulin resistance.…”
Section: Discussioncontrasting
confidence: 53%
“…63,64 The recently discovered adipokine chemerin 65,66 increases insulin sensitivity in 3T3-L1 adipocytes 67 and is essential for normal adipocyte differentiation. 65,66,68 However, it has also been shown to lower glucose tolerance in murine models of obesity/ diabetes 69 and to cause insulin resistance in human skeletal muscle cells, where it was also observed to be pro-inflammatory. 70 Consequently adipose tissue secretes both pro-and anti-inflammatory cytokines which modulate metabolism by altering insulin resistance.…”
Section: Adipose Tissue a Paracrine And Endocrine Organmentioning
confidence: 99%
“…In humans, blood chemerin levels have been described to be correlated with BMI, circulating triglyceride levels, blood pressure, and various other parameters of the metabolic syndrome (Goralski et al 2007, Bozaoglu et al 2009, Mussig et al 2009, Sell et al 2010. In mice, the expression of chemerin in adipocytes is upregulated under a high-fat diet (HFD; Roh et al 2007 and is increased in obese/diabetic db/db mice and in diabetic Psammomys obesus (Goralski et al 2007). The administration of recombinant chemerin has also been reported to reduce glucose uptake, increasing glucose intolerance in db/db mice and diet-induced obesity models .…”
Section: Introductionmentioning
confidence: 99%